10.61533 PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO TERBIT ELEKTRIK DAN ELEKTRONIK - Melita Wangsa; Deara Shinta Lestari; Rizal Ruben Manullang (Jurnal Ilmiah Niaga Bisnis Elektronik, 2025)
This study aims to analyze the effect of financial literacy and financial inclusion on consumer purchasing decisions at Terbit Elektrik and Elektronik Stores in Central Bangka. The main problem raised is the low ability of consumers to understand product technical specifications and impulsive purchasing decisions without financial planning. In addition, the lack of utilization of digital financial services indicates challenges in financial inclusion. This research uses a quantitative approach with survey techniques and data collection through questionnaires. The research sample amounted to 96 respondents who were determined using the simple random sampling method. Data analysis was performed with multiple linear regression using JASP software. The results showed that partially, financial literacy and financial inclusion each had a positive and significant effect on consumer purchasing decisions. Simultaneously, the two variables also have a significant influence on purchasing decisions, with a coefficient of determination (R²) of 0.673. This means that 67.3% of variations in purchasing decisions can be explained by financial literacy and financial inclusion. This study concludes that improving financial literacy and access to formal financial services can encourage consumers to make more rational, efficient and appropriate purchasing decisions. The findings provide important implications for businesses and policy makers to improve financial education and infrastructure to create more financially savvy consumers.